STUDI SEMIOTIKA REPRESENTASI IDENTITAS SELEBGRAM PEREMPUAN BERCADAR DALAM MEDIA SOSIAL INSTAGRAM - Ilvani Fylandita Vristiandaniva; Wiwid Noor Rakhmad (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
Instagram is an alternative communication medium that is effective and efficient in delivering messages. Instagram is considered to be able to form and provide a picture of the reality of everyday life through audio visual, so that it can influence the way of society. The emergence of Instagram social media provides a new label that is often referred to by users, namely Celebrity Instagram or Celebgram for users who have followers or followers above the average and begin to have advertising activities in it. The presence of a celebrity as a new phenomenon in the world of communication, especially social media, namely Instagram, is able to encourage many people with different ethnic, religious and identity backgrounds to be able to take advantage of this advancement in information technology as the main means of establishing mass communication. Including the involvement of veiled women with selebgram status can provide a new picture of the appearance of a veiled woman with a background of cultural identity wearing a Muslim woman. The purpose of this study is to provide an overview in the form of a description of the representation of a veiled woman. How can a veiled woman display her identity in the form of symbols through Instagram social media. This study uses a critical paradigm with a semiotic approach so that it is expected to be able to find the meanings and ideas contained in the account as graded as veiled women. This type of research is descriptive qualitative which uses the semiotic analysis method Charles Sander Peirce uses trichotomy in capturing meaning namely Ground level or functions as a sign, Object, and Interpretant. This study uses representation theory as the main theory to make it easier to evaluate values and see the meaning of a Muslim woman's clothing complete with a veil as an identity in the clothes of a Muslim woman. The results of this study show that three accounts of black veiled women were at the influncer level with the number of followers reaching the premium class designation. At the level of signs or ground it still shows that Instagram is able to become an alternative communication medium for veiled women in sharing all personal activities and activities without limitation between people. This is an awareness of each celebrity who has difficulty communicating face-to-face with many people including the opposite sex. Other findings at the object level show that a number of veiled women tend to be involved in creative activities that support activities that are able to provide more gerka space to become productive women. Level Interpretation provides 4 an overall picture that the representation of a gram of veiled women who have an identity background in wearing clothes as a religious background is integrated with fundamental characteristics. Aware of this as